2011
DOI: 10.2135/cropsci2011.01.0049
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Tolerance and Seasonal Color of Experimental Zoysiagrasses

Abstract: Meyer zoysiagrass {Zoysia japónica Steud.) is the most widely used cultivar in the transition zone of the United States due, in part, to its excellent freezing tolerance. Ten zoysiagrass progeny from crosses between Z. matrella (L.) Merr. x Z japónica or 'Emerald' [Z japónica x Z matrella (L.) Merr. var. pacifica Goudswaard] X Meyer, 'Cavalier' (Z. matrella), and DALZ 0102 (Z. japónica) were evaluated for (i) freezing tolerance, (ii) autumn and spring color, and (iii) a relationship between autumn color and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 19 publications
3
42
1
Order By: Relevance
“…Along with the disease implications, fall fertilization may also have implications for winter hardiness (15). Winter damage was not directly measured in this study, and no patterns related to fertility were observed anecdotally; however, Meyer is a particularly cold-tolerant variety (31,32). Therefore, spring or fall N applications to encourage recovery from large patch are limited in their potential efficacy for reducing large patch symptoms, and fall applications should be approached with caution regarding possible effects on winter hardiness.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Along with the disease implications, fall fertilization may also have implications for winter hardiness (15). Winter damage was not directly measured in this study, and no patterns related to fertility were observed anecdotally; however, Meyer is a particularly cold-tolerant variety (31,32). Therefore, spring or fall N applications to encourage recovery from large patch are limited in their potential efficacy for reducing large patch symptoms, and fall applications should be approached with caution regarding possible effects on winter hardiness.…”
Section: Discussionmentioning
confidence: 83%
“…This large patch study included only one zoysiagrass cultivar, Meyer. Different varieties and germplasm lines have varying rates of establishment (29), cold tolerance and greenup after winter dormancy (31,33), recovery from damage or sod harvest (30), and susceptibility to and ability to recover from large patch (28,32). Different cultivars may respond differently to various combinations of disease and cultural practices, including N fertility.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Z. japonica, which became dormant later in the fall of 2008 also underwent green‐up later in the spring of 2009, which is different from the results of Okeyo et al . (). Although they found a positive correlation between fall color and spring color in four out of eight occasions, they also mentioned Meyer was always in the lowest statistical group for fall color and the best group for spring green‐up.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the correlation between low temperature tolerance and fall green color retention was similar to the results from two other studies on zoysiagrass (Okeyo et al . ) and buffalograss ( Buchloë dactyloides (Nutt.) Engelm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation